Silver nanowires on acid-alkali-treated titanium surface: Bacterial attachment and osteogenic activity. Issue 18 (15th December 2019) - Zhang, Chao; Lan, Jinping; Wang, Shuo; Han, Shuguang; Yang, Hao; Niu, Qimeng; Wang, Jing; Wang, Qianqian; Xiang, Yuhong; Wu, Yuwei; Zhang, Xuejiao; Lin, He; et al.
Abstract: In the present work, a nanoscale porous surface was gradually prepared on Ti surface by two-step method of acid corrosion and NaOH–H2 O2 mixing treatment. This led to the formation of a TiO2 coating at the surface of the underlying Ti substrate. Then, silver nanowires were deposited on the nanostructured surface by spin-coating technology. The nanowires were found to be evenly introduced into the nanostructured TiO2 coating. The modified Ti surface showed good wettability and protein adsorption capacity. More importantly, in-vitro cellular and bacterial assays indicated that the modified Ti surface possessed not only the excellent adhesion and differentiation abilities for osteoblasts but also relatively strong antimicrobial capacities for both S. aureus and E. coli . The results suggest that such modified Ti surfaces greatly prefer the initial adhesion of osteoblast-like cells over the initial adhesion of bacteria. The surface modification that we made to Ti substrate can promisingly meet clinical requirements.